A polygon scaled boundary finite element formulation for transient coupled thermoelastic fracture problems. (December 2020) - Ooi, E.T.; Iqbal, M.D.; Birk, C.; Natarajan, S.; Ooi, E.H.; Song, C.
Highlights: A SBFEM formulation for transient coupled thermoelasticity is proposed. Supplementary shape functions lead to accurate stress fields at stress concentrators. No post-processing techniques needed to compute transient stress intensity factors. Models the singular stress field with a single polygon. Refinement on polygon boundary increases accuracy of singular stresses. Abstract: The scaled boundary finite element method is developed for transient thermoelastic fracture analysis. To enable this, a set of novel shape functions are derived considering thermoelastic equilibrium. The salient features of the proposed framework are: (a) can be formulated on polygons with an arbitrary number of sides leading to flexible mesh generation and (b) facilitates an accurate and direct evaluation of the stress intensity factors from their definition without resorting to any post-processing techniques using relatively coarse meshes. Several numerical benchmark problems demonstrate the aforementioned features of the technique.